Theoretical study of the elastic properties of the minerals Cu3TMSe4 (TM = V, Nb, Ta) by means of atomistic first-principles calculations (2011)
The elastic properties of the family of the iso-structural minerals Cu3VSe4, Cu3NbSe4 and Cu3TaSe4 have been calculated for the first time using the state of the art in first-principle atomistic calculations, using the Density Functional Theory and the Approach of the Generalized Gradient for the Functional of the exchange-correlation energy. The calculated elastic properties are the volumetric modulus (B), the elastic constants (c11, c12 and c44), the Zener anisotropy factor (A), the isotropic shear modulus (G), the Young modulus (Y), and Poisson's ratio (ν). Through these quantities we have also calculated other thermodynamic properties such as the average velocity of transverse (st) and longitudinal (sl) sound and Debye temperature (ΘD). The calculated values of B, c11, c12 and c44, G, Y, and ν lead us to the conclusion that these compounds are compressible, fragile and brittle.